Barriers and facilitators related to the health care system in spinal cord injury - Abdul-Ganiyu Fuseini*; Patience Aniteye; Gideon Kofi-Helegbe (Tehran University of Medical Sciences, 2018)
Background & Aim: The majority of studies on the facilitators and barriers to functioning in spinal cord injury (SCI) focussed on physical and psychosocial barriers/facilitators, with little emphasis on barriers and facilitators related to the health care system. The purpose of the present study was to explore the barriers/facilitators in the health care system to the functioning of persons with SCI. Methods & Materials: The present study was a qualitative descriptive design that was conducted at the Tamale Teaching Hospital in the Northern Region of Ghana. The study employed the purposive sampling technique with the Neurosurgical Unit of the Hospital as an outlet for the selection of the sample. Thirteen participants were interviewed using an interview guide. The sample was determined by saturation and the data was analysed using thematic analysis. Result: Treatment and management issues, health staff issues and health education issues respectively emerged as the main themes of the present study. Sub-themes such as long-term analgesic use, herbal treatment, lack of health education and high cost of treatment emerged as barriers to functioning of persons with SCI. While physiotherapy and health education were identified as facilitators to functioning, surgery emerged as both a barrier and a facilitator to functioning.  Conclusion: Addressing the barriers related to the health care system on the functioning of persons with SCI and improving on the few existing facilitators to functioning would help improve the general wellbeing of persons with SCI and also assist in their adjustment to the injury.